High‐resolution TanDEM‐X DEM: An accurate method to estimate lava flow volumes at Nyamulagira Volcano (D. R. Congo). Issue 6 (30th June 2015) - Albino, F.; Smets, B.; d'Oreye, N.; Kervyn, F.
Abstract Nyamulagira and Nyiragongo are two of the most active volcanoes in Africa, but their eruptive histories are poorly known. Assessing lava flow volumes in the region remains difficult, as field surveys are often impossible and available Digital Elevation Models (DEMs) do not have adequate spatial or temporal resolutions. We therefore use TerraSAR‐X add‐on for Digital Elevation Measurement (TanDEM‐X) interferometry to produce a series of 0.15 arc sec (∼5 m) DEMs from between 2011 and 2012 over these volcanoes. TanDEM‐X DEMs have an absolute vertical accuracy of 1.6 m, resulting from the comparison of elevation with GPS measurements acquired around Nyiragongo. The difference between TanDEM‐X‐derived DEMs from before and after the 2011–2012 eruption of Nyamulagira provides an accurate thickness map of the lava flow emplaced during that activity. Values range from 3 m along the margins to 35 m in the middle, with a mean of 12.7 m. The erupted volume is 305.2 ± 36.0 × 106 m3. Height errors on thickness depend on the land covered by the flow and range from 0.4 m in old lavas to 5.5 m in dense vegetation. We also reevaluate the volume of historical eruptions at Nyamulagira since 2001 from the difference between TanDEM‐X and SRTM 1 arc sec DEMs and compare them to previous work. Planimetric methods used in literature are consistent with our results for short‐duration eruptions but largely underestimate the volume of the long‐lived 2011–2012 eruption. Our new estimates of erupted volumes suggest that the mean eruption rate and the magma supply rate were relatively constant at Nyamulagira during 2001–2012, respectively, 23.1 m3 s−1 and 0.9 m3 s−1.